2015
DOI: 10.1002/2015ja021319
|View full text |Cite
|
Sign up to set email alerts
|

The effect of including field‐aligned potentials in the coupling between Jupiter's thermosphere, ionosphere, and magnetosphere

Abstract: Jupiter's magnetosphere‐ionosphere‐thermosphere system drives the brightest, steadiest aurora in our solar system. This emission is the result of an electrical current system, which couples the magnetosphere to the planetary atmosphere in an attempt to enforce the corotation of the middle magnetospheric plasma. Field‐aligned currents transfer angular momentum from the atmosphere to the magnetosphere. In the equatorial plane, the field‐aligned currents diverge into radially outward currents, which exert a torqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 52 publications
1
53
0
Order By: Relevance
“…T is the weighted average of all the horizontal winds and is the thermospheric neutral velocity that the magnetosphere sees (see Smith & Aylward, 2008, for details on how this is calculated). The full details on how these modules are coupled together can be found in Smith and Aylward (2009), Yates et al (2012Yates et al ( , 2014, and Ray et al (2015). These two angular velocities combined with the height-integrated Pedersen conductance from the ionosphere module enable us to self-consistently determine the MI coupling currents and the resultant heating of the atmosphere due to the magnetospheric interaction.…”
Section: Coupled Mit Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…T is the weighted average of all the horizontal winds and is the thermospheric neutral velocity that the magnetosphere sees (see Smith & Aylward, 2008, for details on how this is calculated). The full details on how these modules are coupled together can be found in Smith and Aylward (2009), Yates et al (2012Yates et al ( , 2014, and Ray et al (2015). These two angular velocities combined with the height-integrated Pedersen conductance from the ionosphere module enable us to self-consistently determine the MI coupling currents and the resultant heating of the atmosphere due to the magnetospheric interaction.…”
Section: Coupled Mit Modelmentioning
confidence: 99%
“…Works by Yates et al (2012Yates et al ( , 2014 have shown that using a fixed Pedersen conductance, instead of a variable one, in this region does not significantly alter the local thermospheric dynamics and heating if we consider perfect coupling between the ionosphere and magnetosphere, that is, there are no field-aligned potential (FAP) drops. Work by Ray et al (2015) was the first to include FAPs in a MIT coupling model and found that neutral temperatures and flows were changed by a few percent when compared to the same MIT model without FAPs. The ionosphere and precipitating particles in this region are only recently being investigated by Jupiter's polar orbiting Juno spacecraft which will undoubtedly shed light on the conditions in this relatively unexplored region of Jupiter's upper atmosphere and high-latitude magnetosphere.…”
Section: Limitations Of the Current Modelmentioning
confidence: 99%
See 3 more Smart Citations